Perlindungan Terhadap Aktivitas Perempuan di Bidang Politik dan Tenaga Kerja - Munawir Munawir (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to analyze the protection of women's activities in politics and labor in the context of law and policy in Indonesia. Using a qualitative method with a juridical-sociological approach, this study examines regulations that guarantee gender equality and the structural obstacles faced by women. The results show that despite various regulations such as Law Number 7 of 1984 concerning the Ratification of the CEDAW Convention and the Manpower Act, their implementation is still not optimal. Women still face discrimination, limited access, and gender stereotypes in both politics and the job market. This study emphasizes the importance of consistent law enforcement, gender education, and policy reform to create a fair and equal space for women's participation.